1998
DOI: 10.1104/pp.118.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Granule-Bound Starch Synthase Isoform Found in the Pericarp of Wheat

Abstract: Waxy wheat (Triticum aestivum L.) lacks the waxy protein, which is also known as granule-bound starch synthase I (GBSSI). The starch granules of waxy wheat endosperm and pollen do not contain amylose and therefore stain red-brown with iodine. However, we observed that starch from pericarp tissue of waxy wheat stained blue-black and contained amylose. Significantly higher starch synthase activity was detected in pericarp starch granules than in endosperm starch granules. A granule-bound protein that differed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 44 publications
3
77
0
Order By: Relevance
“…A recent phylogenetic analysis of the Rosaceae has shown two loci encoding GB-SSI in all subfamilies (Evans et al, 2000), suggesting that more than one isoform of GBSSI may be active in some other dicot species, although only one GBSSI gene has been found in the genome sequence of Arabidopsis and only one active form has been identified in potato. In wheat, two structurally distinct isoforms are expressed in different tissues (Fujita and Taira, 1998;Nakamura et al, 1998;Vrinten and Nakamura, 2000), and there is evidence for at least two genes that encode GBSSI in rice, barley, and maize (Vrinten and Nakamura, 2000).…”
Section: Differences In the Products Of Gbssi Isoformsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent phylogenetic analysis of the Rosaceae has shown two loci encoding GB-SSI in all subfamilies (Evans et al, 2000), suggesting that more than one isoform of GBSSI may be active in some other dicot species, although only one GBSSI gene has been found in the genome sequence of Arabidopsis and only one active form has been identified in potato. In wheat, two structurally distinct isoforms are expressed in different tissues (Fujita and Taira, 1998;Nakamura et al, 1998;Vrinten and Nakamura, 2000), and there is evidence for at least two genes that encode GBSSI in rice, barley, and maize (Vrinten and Nakamura, 2000).…”
Section: Differences In the Products Of Gbssi Isoformsmentioning
confidence: 99%
“…The leaves and stem of waxy rice, the leaves and pericarp of waxy maize, the pericarp of waxy wheat, and the pods, leaves, and nodules of lam pea all contain amylose, implying that another gene (or genes) controls amylose production in the organs of these plants (Shannon and Garwood, 1984;Taira et al, 1991;Denyer et al, 1997;Nakamura et al, 1998). A protein of similar molecular mass, antigenic properties, and N-terminal sequence to GBSSI has been detected in the leaves of lam pea , and a cDNA encoding a GBSSI-like starch synthase has been isolated from waxy wheat and shown to be expressed in nonstorage tissues (Fujita and Taira, 1998;Nakamura et al, 1998;Vrinten and Nakamura, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSI probably plays important role(s) in starch biosynthesis in plants since it has no multiple isoforms, unlike all other SS types having more than two isoforms in rice (SSII, SSIII, SSIV, and GBSS; Hirose and Terao, 2004), maize (SSII; Harn et al, 1998), kidney bean (Phaseolus vulgaris; SSII and GBSS; Matsui et al, 2003;Isono et al, 2004), and wheat (GBSS; Fujita and Taira, 1998;Nakamura et al, 1998). Mu-Forster et al (1996) reported that more than 85% of the SSI in maize endosperm is associated with starch granules.…”
mentioning
confidence: 99%
“…The GBSS is encoded by the Waxy locus in cereals and is responsible for elongation of amylose [25,26]. GBSS can also be further separated to GBSSI that primarily appears in storage tissues and GBSSII that mostly presents in the leaves and other non-storage tissues and is responsible for the synthesis of transient starch [27][28][29][30][31][32]. Apart from main glucan chain, starch also contains branch chain that is synthesized by SBE and DBE.…”
mentioning
confidence: 99%